A New Family of High-Affinity Transporters for Adenine, Cytosine, and Purine Derivatives in Arabidopsis - Gillissen, Bernd (American Society of Plant Biologists, 2000)
In many organisms, including plants, nucleic acid bases and derivatives such as caffeine are transported across the plasma membrane. Cytokinins, important hormones structurally related to adenine, are produced mainly in root apices, from where they are translocated to shoots to control a multitude of physiological processes. Complementation of a yeast mutant deficient in adenine uptake (fcy2) with an Arabidopsis cDNA expression library enabled the identification of a gene, AtPUP1 (for Arabidopsis thaliana purine permease1), belonging to a large gene family (AtPUP1 to AtPUP15) encoding a new class of small, integral membrane proteins. AtPUP1 transports adenine and cytosine with high affinity. Uptake is energy dependent, occurs against a concentration gradient, and is sensitive to protonophores, potentially indicating secondary active transport. Competition studies show that purine derivatives (e.g., hypoxanthine), phytohormones (e.g., zeatin and kinetin), and alkaloids (e.g., caffeine) are potent inhibitors of adenine and cytosine uptake. Inhibition by cytokinins is competitive (competitive inhibition constant [Formula: see text] (i) = [Formula: see text] μ [Formula: see text]), indicating that cytokinins are transported by this system. AtPUP1 is expressed in all organs except roots, indicating that the gene encodes an uptake system for root-derived nucleic acid base derivatives in shoots or that it exports nucleic acid base analogs from shoots by way of the phloem. The other family members may have different affinities for nucleic acid bases, perhaps functioning as transporters for nucleosides, nucleotides, and their derivatives.